Graphic Novels: Understanding how Fifth Graders Read Literary Text through Eye Movement Analysis - Yusof, Suriani Mohd (Archīum Ateneo, 2024)
The use of multimodal texts as a teaching resource is believed to be one of the fundamental requirements in keeping abreast with the rapid evolvement of literacy. This practice is reflected in the teaching of literature at primary schools in Malaysia when graphic novels, an example of a multimodal text, are introduced as one of the contemporary literary texts. The unique combination of language and images to make meaning in new ways is considered to be one of the main attributes why graphic novels are relevant in promoting multimodality in literature learning. Although its benefits are extensively explored, little research has been conducted to investigate how graphic novels are read. Do the readers actually effectively use the textual (language) and visual (images) elements when reading graphic novels? To this end, a study to investigate the patterns of visual behaviour of good and poor readers was conducted to observe the moment-by-moment processes during reading. Forty-nine Year 5 primary schoolers participated in a reading experiment using the Tobii TX300 eye tracking machine. Twelve pages of graphic novels from the Hardy Boys and the Nancy Drew series were used as stimuli. Utilizing gaze plot and heat map analysis as the eye movement measure, this paper reports the eye movement behaviours of these young readers when reading graphic novels in three categories, namely, the sequence of panels, the reading path and the textual or visual focus. Results indicate that the participants, irrespective of their reading ability, had difficulty to follow the correct sequence of panels when the layout of the stimuli involves ‘staggering’ and ‘blockage’ manipulations. Although the majority of the participants followed the “left-to-right and down order” or the “Z-path”, when reading graphic novels, greater amount of attention was given to the textual elements compared to the visual features which were overlooked when navigating the stimuli. Results from this study highlight the educational implications that the importance of visual processing and its integration with textual elements should be taught to young readers to assist comprehension.